Determinan Profitabilitas: CSR, Tax Avoidance, Struktur Aset, dan Ukuran Perusahaan Non-Cyclicals - Nopiani Indah (Yayasan Literasi Sains Indonesia, 2025)
This study aims to examine the effect of Corporate Social Responsibility (CSR), tax avoidance, asset structure, and firm size on profitability in consumer non-cyclical companies listed on the Indonesia Stock Exchange during 2019–2023. The research employs a quantitative approach with panel data, involving 31 companies and 155 observations. Profitability is measured using Return on Assets (ROA), while CSR, tax avoidance, asset structure, and firm size are measured using the CSR index, Effective Tax Rate (ETR), fixed assets to total assets ratio, and the natural logarithm of total assets, respectively. Panel regression analysis using the random effect model is applied to test the hypotheses. The results indicate that only tax avoidance has a significant negative effect on profitability, whereas CSR, asset structure, and firm size do not show significant impacts. These findings suggest that efficient tax management plays a more substantial role in short-term net income improvement than social responsibility or firm scale. The practical implication encourages corporate management to optimize tax strategies, asset efficiency, and growth management while maintaining long-term sustainability and social responsibility.